Optimizing herbicide selection for pre-emergence control of itchgrass and cypressvine morningglory in sugarcane - Araldi de Castro, Rosilaine; de Castro, Sérgio Gustavo Quassi; Quassi de Castro, Saulo Augusto; Piassa, Alexandre; Soares, Gabriella Onila do Nascimento; Tropaldi, Leandro [UNESP]; Christofoletti, Pedro Jacob (Taylor & Francis, 2024)
The aim of this study was to assess the efficacy of herbicides in association to control Rottboellia exaltata and Ipomoea quamoclit during pre-emergence while also to evaluate the potential impact on the sugarcane. The experimental design employed a randomized block with seven treatments and four replications. The treatments were: 1–no herbicide application; 2–indaziflam + sulfentrazone; 3–indaziflam + diclosulam; 4–indaziflam + tebuthiuron; 5–flumioxazin + diclosulam, 6–flumioxazin + pyroxasulfone and 7–clomazone + sulfentrazone. The evaluated parameters were: percentage of weeds control, green coverage percentage (Canopeo® system), weed biomass (g m−2), itchgrass height, and sugarcane tiller. Several herbicide associations have been proven effective alternatives for managing itchgrass and cypressvine morningglory. The most successful treatments for itchgrass control were indaziflam + tebuthiuron (100%) and indaziflam + diclosulam (97%), whereas for cypressvine morningglory, the betters were indaziflam + sulfentrazone (97%), indaziflam + diclosulam (98%), indaziflam + tebuthiuron (97%), flumioxazin + diclosulam (94%), and clomazone + sulfentrazone (96%). All treatments reduced the weed biomass, with indaziflam + tebuthiuron being the safest option for protecting sugarcane.
Keywords: canopeo®; ipomoea quamoclit; rottboellia exaltata; selectivity; Sugarcane